Power system operation & control: the teaching module - Mohd Herwan, Sulaiman; Muhammad Ikram, Mohd Rashid; Omar, Aliman (Penerbit UMP, 2017)
This teaching module purposely prepared to facilitate the teaching and learning process for course BEE4173 Power System Operation & Control which is offered to undergraduate students at the Fakulti Kejuruteraan Elektrik & Elektronik (FKEE) Universiti Malaysia Pahang.